Cultural pasts : essays in early Indian history - Thapar, Romila (New Delhi : Oxford University Press, 2010)
This collection of papers and lectures on early lectures on early Indian history by one of India's foremost historians focuses on historiography and the changing dimensions of social and cultural history.
Contents : Chapter 1. Histography--Chapter 2. Social and cultural transactions--Chapter 3. Archaeology and history --Chapter 4. pre-Mauryan and Mauryan India--Chapter 5. Forms of exchange--Chapter 6. The society of heroes in the epics and the later tradition of venerating heroes-- Chapter 7. Genealogics and origin myths--Chapter 8. The social context of the renouncer--Chapter 9. The present in the past.
Includes bibliographical references and index.
Keywords: India -- Ancient History; India -- History -- To 324 B.C.; India -- Civilization; India -- History -- 324 B.C.-1000 A.D.